Inside Back Cover: Atomically Dispersed Molybdenum Catalysts for Efficient Ambient Nitrogen Fixation (Angew. Chem. Int. Ed. 8/2019). Issue 8 (16th January 2019) - Han, Lili; Liu, Xijun; Chen, Jinping; Lin, Ruoqian; Liu, Haoxuan; Lü, Fang; Bak, Seongmin; Liang, Zhixiu; Zhao, Shunzheng; Stavitski, Eli; Luo, Jun; Adzic, Radoslav R.; et al.
Abstract : Electrocatalytic N2 reduction under ambient conditions offers a promising carbon‐free strategy toward clean and sustainable NH3 production. In their Communication on page 2321 ff., J. Luo, R. R. Adzic, H. L. Xin et al. report single molybdenum atoms anchored on nitrogen‐doped porous carbon. The catalyst achieves a high NH3 yield rate, Faradaic efficiency, and stability at room temperature because of a high density of active sites within a hierarchically porous carbon framework.